The Impact of Profitability on Market Value Added: Evidence from Turkish Informatics and Technology Firms - Akgun, Ali Ihsan; Samiloglu, Famil; Oztop, Ali Osman (International Journal of Economics and Financial Issues, 2018)
The purpose of this study is to examine empirically the relationship between economic value added (EVA), return on assets (ROA), and return on equity (ROE) with market value added (MVA) in Istanbul Stock Exchange (BIST). This study also examine the performances implemented by Turkish Informatics and Technology Firms during the global financial crisis of 2008-2009. Using the experimental data were drawn from a panel consisting of 13 Turkey firms listed in the BIST, from informatics and technology companies, observed over the ten-year period. Multicollinearity various regression models were examined in order to test the hypotheses included in the examined literature. In the research methodology such as fixed effects and random effects were examined in order to test our hypotheses proposed. Finally, evidence is presented that economic value added has a negative and significant relationship with MVA, while ROA and ROE have no significant relationship with MVA in the long-term. Keywords: Market Value Added, Economic Value Added, Financial Crisis, Return on Asset, Return on Equity. JEL Classifications: G32, M40, M41.